EFFECT OF CHEMICAL ADDITION ON THE PACT PROCESS UNDER DIFFERENT ADSORPTION/DESORPTION AND BIODEGRADATION CONDITIONS - Tri Widjaya (Purifikasi, 2008)
Many kinds of hazardous waste water contain a variety of different biologically inhibitory compounds that affect the efficiency of biological treatment. The majority of the components in complex waste water may be easily biodegraded if the inhibitory compounds are removed by physical adsorption. Powdered activated carbon (PAC) has been used to decrease the concentration of inhibitory compounds in the powdered activated carbon treatment (PACT) process. The combined biological and physical adsorption mechanisms decrease the concentration of inhibitory compounds using the large adsorptive capacity of PAC in the PACT reactor making the reactor resilient to changes in operation and wastewater composition. The main aims of the study were to evaluate the performance of PACT process for shock loading of substances with different adsorbility/desorbility to PAC and biodegradability. This experiment used synthetic wastewater with polypepton as the main component. A continuous bioreactor was used, with a flow rate of 7 l h-1. The pH value was adjusted from 6.5 to 7.5 by the addition of 0.01 N-sodium hydroxide or 0.01 N sulphuric acid. Dissolved oxygen concentration was maintained at around 2 mg/L by aeration. Coal-based PAC (Mitsubishi chemical: Diahope 008 N) at a concentration of 1,500 mg/L was added to the aeration tank of PACT reactor. Mixed liquor suspended solids (MLSS) in the aeration tank were maintained at 4,500 mg/L (biomass = 3,000 mg/L, PAC = 1,500 mg/L) and at 3,000 mg/L for the control reactor. Solid retention time (SRT) was about 15 days. The 3,5-dichlorophenol (3,5-DCP), bromo phenol (BP) and bromo acetic acid (BAA) were chosen as toxic compounds. The PACT reactor showed high performance for 3,5-DCP, 3-BP and BAA removals. In the PACT process, 3,5-DCP was removed only by adsorption, but the 3-BP was removed by biodegradation and adsorption. This is due to the difference in biodegradabilities between 3,5-DCP and 3-BP irrespective of similar absorbilities. Although adsorption was the main mechanism to remove 3,5-DCP with low desorbility, both adsorption and biodegradation contributed to remove of 3-BP and BAA with high desorbilites. In the PACT reactor, the 3-BP and BAA were biodegraded both directly and indirectly. For indirect biodegradation, both substances were adsorbed on PAC and then desorbed from PAC after the shock loading, and finally they are biodegraded. Although the biodegradability and desorbility of BAA was higher than that of 3-BP, the biodegraded BAA was 54% smaller than that of 3-BP. This is because the biodegradability of BAA in the PACT process was due to the chemical desorbility. The performance of the PACT processes was affected by adsorbility and desorbility of the chemicals, in which the desorbility of the chemicals had significant impacts on the biodegradability.